Nominal derivation in the Umahua language - Huamancayo Curi, Edinson (2006)
The purpose of this paper is to report on some aspects related to nominal derivation in the Umahua language, which is considered virtually extinct, based on the analysis of data collected from interviews with two bilingual (Umahua-Spanish) speakers in 2004 and from texts written by one of them in the same year. The data that complement this information are based on previous work on the Umahua and Cocama languages (both of which are part of the Tupi-Guarani linguistic family of Peru). In Umahua, derived nouns are formed by attaching the suffixes -suri, -wara, -qui- ra and -huasu to a root or radical of the same or different lexical category (derivation by suffixation) and by combining roots and radicals (derivation by composition). Compound nouns have as initial component a verbal or nominal form and as final component the nominal form siru or tupa.